2018
DOI: 10.1371/journal.pone.0207394
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the influence of resiliency on physician trust in patients: An empirical study of Chinese incidents

Abstract: BackgroundThe tension in doctor-patient relationships is becoming progressively greater due to the high expectations of patients and the physicians’ work pressure. Recent studies have addressed factors which affect the tension of doctor-patient relationships, and our study continues this trend by looking at the influence of resiliency and physician trust in the patient (PTP), that is, how much the doctor trusts the patient.MethodsBased on a survey of 329 physicians, a descriptive analysis of measured data was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 38 publications
4
21
0
Order By: Relevance
“…HCPs indicated self-referral patients or families half believed their given regimens, which undermines con dence to communicate with patients. As reported by Sun et al [38], we found those subtle pressure tense staff-patient relationship. Our study suggest that the situation is more complex and creates a vicious cycle.…”
Section: Discussionsupporting
confidence: 86%
“…HCPs indicated self-referral patients or families half believed their given regimens, which undermines con dence to communicate with patients. As reported by Sun et al [38], we found those subtle pressure tense staff-patient relationship. Our study suggest that the situation is more complex and creates a vicious cycle.…”
Section: Discussionsupporting
confidence: 86%
“…The SDS has 20 items in total, which are divided into four dimensions: mental-emotional (two items about depressed mood and crying), physical (8 items about daytime mood difference, sleep disturbance, decreased appetite, decreased libido, decreased body mass, constipation, tachycardia, and fatigue), psychomotor disorder (2 items: psychomotor hysteresis and agitation), and the psychological disorder (8 items about confusion, hopelessness, irritability, indecision, self-depreciation, emptiness, rumination about suicide, and dissatisfaction). For each item the response choices are "A little of the time" (1), "Some of the time" (2), "Good part of the time" (3), and "Most of the time" (4), and items 2, 5,6,11,12,14,16,17,18, and 20 are scored inversely. The sum of the scores of all 20 items is the raw score, which is then multiplied by 1.25 and rounded to the nearest whole number to get the standard score.…”
Section: Measures Usedmentioning
confidence: 99%
“…However, a recent episode of the CCTV program "News 1+1" reported that the data of doctor-patient disputes showed a continuously rising trend. The doctor-patient conflict risk at hospitals has always existed but, especially in recent years, events of violence against medical professionals have occurred frequently [5], seriously affecting the PH of doctors.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in our review stressed uncertainties and vulnerabilities as antecedents and/or consequences of (dis)trust. As these uncertainties and vulnerabilities become explicit as 'pre-trust' or 'post-hoc trust dynamics' conditions, some authors describe a 'crisis' of professionals' trust in patients (Sun et al, 2018), suggesting SOUSA-DUARTE ET AL.…”
Section: Features Of Healthcare Professionals' Trust In Patientsmentioning
confidence: 99%